2002
DOI: 10.1002/art.10427
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tacrolimus in rheumatoid arthritis patients who have been treated unsuccessfully with methotrexate: A six‐month, double‐blind, randomized, dose‐ranging study

Abstract: Objective. To assess the efficacy, safety, and optimal dose of tacrolimus monotherapy in patients with rheumatoid arthritis (RA).Methods. This phase II, randomized, doubleblind, placebo-controlled monotherapy study was set in 12 community sites and 9 university-based sites. Two hundred sixty-eight patients with RA who were resistant to or intolerant of methotrexate (mean dose 15.2 mg/ week) and had active disease for at least 6 months (mean tender joint count 28.2, mean erythrocyte sedimentation rate 46.5 mm/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 19 publications
(20 reference statements)
7
97
2
1
Order By: Relevance
“…Tac also suppresses the production of cytokines such as IL -2 and TNFα 11,12) . The usefulness of Tac for RA has been demonstrated in double -blind, placebo -controlled, parallel -group studies and controlled studies compared with other drugs 13,14) . Tac up to 3 mg/daily is approved to be used for the patients with RA in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Tac also suppresses the production of cytokines such as IL -2 and TNFα 11,12) . The usefulness of Tac for RA has been demonstrated in double -blind, placebo -controlled, parallel -group studies and controlled studies compared with other drugs 13,14) . Tac up to 3 mg/daily is approved to be used for the patients with RA in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…FK506 exerts its immunosuppressive effects by inhibiting calcineurin phosphatase, an enzyme involved in activation of transcription factor NF-AT, required for the expression of cytokine genes in T cells [19]. FK506 is reported to suppress the onset of CIA in prophylactic treatment [26,29], and is also effective in the treatment of RA [30]. We have shown that FK506 reduces both levels of IL-1b [25,31] and IL-6 [25] in paw tissue during therapeutic treatment of AIA.…”
Section: Figmentioning
confidence: 99%
“…FK506 is an immunosuppressive agent that specifically inhibits T cell activation via calcineurin inhibition [20,21]. FK506 has been shown to be effective in RA patients failing MTX treatment [22,23]. In the present study, we attempted to characterize anti-arthritic properties of LEF, by comparing with MTX and FK506.…”
Section: Introductionmentioning
confidence: 99%